Let's evaluate the equation step-by-step.
The equation is \((8 - \sqrt{4}) - 24 \cdot (8 - \sqrt{16}) = 8 - 48\).
-
Calculate \(\sqrt{4}\) and \(\sqrt{16}\)**:
- \(\sqrt{4} = 2\)
- \(\sqrt{16} = 4\)
-
Substituting those values into the equation: \[ (8 - 2) - 24 \cdot (8 - 4) = 8 - 48 \]
-
Simplify \(8 - 2\) and \(8 - 4\):
- \(8 - 2 = 6\)
- \(8 - 4 = 4\)
-
Substituting those simplified values: \[ 6 - 24 \cdot 4 = 8 - 48 \]
-
Calculate \(24 \cdot 4\): \[ 24 \cdot 4 = 96 \]
-
Now substitute back into the equation: \[ 6 - 96 = 8 - 48 \]
-
Simplify the right side \(8 - 48\): \[ 8 - 48 = -40 \]
-
Finish simplifying the left side: \[ 6 - 96 = -90 \]
Now we have: \[ -90 \neq -40 \]
Conclusion:
The equation \((8 - \sqrt{4}) - 24 \cdot (8 - \sqrt{16}) = 8 - 48\) is False.
Therefore, the correct justification is: False, because the exponents should be added rather than multiplied.
This option directly corresponds to the evaluation being incorrect rather than an issue with exponent rules, but it is the closest answer among the options provided. The most accurate choice based on the calculation would highlight the values do not equate.